Gastrointestinal Stromal Tumours: A Review on Genetics, Pathology, Risk Stratification, Clinical Characteristics, Investigation, and Treatment - Md Tanveer Adil; Jayesh Sagar; Partha Das; Vigyan Jain (European Medical Journal Oncology, 2016)
Gastrointestinal stromal tumours (GISTs) are the most common mesenchymal tumours of the gastrointestinal tract, arising from the interstitial cells of Cajal. They are known to occur in all parts of the gastrointestinal tract from the oesophagus to the anorectum, with the stomach being the most commonly affected organ (60%). GISTs are commonly known to occur within the fifth and sixth decades of life, carry an equal predisposition between females and males, and are associated with tyrosine-protein kinase (KIT) or platelet-derived growth factor receptor alpha (PDGFRA) mutations in 85–90% of cases. Familial syndromes associated with GISTs are neurofibromatosis Type 1, Carney’s triad (gastric GIST, pulmonary chordoma, and paraganglioma), Carney–Stratakis syndrome (GIST and paraganglioma), and familial GISTs. Lesions vary in size from a few mm to >30 cm, with a median size between 5 and 8 cm. Immunohistochemical staining with KIT and DOG1 show the highest sensitivity for GISTs. While 20% of GISTs are diagnosed asymptomatically, and 10% at autopsy, 70% are symptomatic. Bleeding followed by abdominal pain and a mass growth are the most common symptoms. Forty to fifty percent of GISTs are biologically malignant. Malignant GISTs spread haematogenously to the liver and peritoneum, while lymphatic spread is rare. Risk stratification subdivides GISTs into very low, low, intermediate, and high-risk groups. Computed tomography (CT) scan is the mainstay of diagnosis, though they are often incidentally detected on endoscopy. Surgery offers the best chance of cure in resectable lesions, while tyrosine kinase inhibitors are the treatment of choice in non-resectable and metastatic GISTs. Neoadjuvant and adjuvant tyrosine kinase inhibitors increase resectability, time to recurrence, recurrence-free survival, and overall survival in GISTs.